ChemInform Abstract: Synthesis of Enantioenriched Tertiary Boronic Esters by the Lithiation/Borylation of Secondary Alkyl Benzoates. Issue 15 (15th April 2014) - Pulis, Alexander P.; Blair, Daniel J.; Torres, Eva; Aggarwal, Varinder K.
Abstract Unactivated secondary Tib esters react to afford a range of neopentyl boronic esters, which are transformed to the corresponding tertiary alcohols in high yields and generally high enantioselectivities.